Immediate Loaded Post Extraction Implant and Connective Graft-Guided Bone Regeneration: A Case Report - Calderon, Ivan; Alvitez-Temoche, Daniel; Espinoza-Carhuancho, Fran; Mendoza, Roman; Mauricio, Franco; Mayta-Tovalino, Frank (Odovtos - International Journal of Dental Sciences, 2024)
This case report describes the clinical and therapeutic approach used in a 32-year-old female patient with a tooth fracture in tooth 22. The patient, with no history of systemic disease, presented with a chronic periapical lesion and a cervical fracture in the affected tooth. Treatment included atraumatic extraction of the tooth, followed by placement of a 3.75 x 10mm post-extraction implant with immediate loading and guided bone regeneration. The minimally invasive surgical technique was employed using the Dentoflex® drilling sequence. The primary stability of the implant, measured in 37 Newtons of torque, allowed the placement of a prefabricated metal abutment for the subsequent cemented crown. Bone regeneration of the interimplant space was successfully performed, supplemented by connective grafting due to the patient's thin gingival phenotype. Postoperative follow-up, including controls at 7, 14 days and four months, showed a satisfactory conformation of the gingival margin and papillary tissue, consolidating the success of the treatment.